May I buy strawberries? : a study of control of money and household spending in marriage in the northernmost borderland of Sweden - Juntti-Henriksson, Ann-Kristin (Luleå tekniska universitet, Medier ljudteknik och upplevelseproduktion och teater, 2003)
A study consisting of interviews and observations of women from the northernmost borderland of Sweden (Tornedalen area) has been conducted. Sweden is generally considered to be one of most gender equal cultures in the world. However, in some parts of the rural areas of northern Sweden, the population is strongly dominated by men, which could suggest a cultural-lag in gender equality. By using the women's narratives the study focus on household spending and the control of money in marriage. The gendered patterns in the "social and sexual contracts" between the men and the women are discussed. Women felt that they were responsible for the day-to-day management of the household money even when they did not have the real control over the money. Women showed, in general, a greater concern of any earnings to the housekeeping than did their partners. In many cases, the male dominance in marriage was clearly evident in terms of household money spending since women took much less for their personal needs than did the men. The women, themselves, explained this male dominance by the local culture with its traditional gender roles (as compared to other areas of Sweden). The gendered differences could refer to culturally formed patterns of masculinity and feminity, that is, forms of behaviour of men and women, respectively, explained by a cultural-lag. It seems that the female and male roles have been strongly cemented in this part of Sweden during the late twentieth century. Godkänd; 2003; 20101126 (akijuh)